Characterization of diverse bacteriohopanepolyols in a permanently stratified, hyper-euxinic lake. (June 2022) - O'Beirne, Molly D.; Sparkes, Robert; Hamilton, Trinity L.; van Dongen, Bart E.; Gilhooly, William P.; Werne, Josef P.
Highlights: A novel diunsaturated aminotriol is associated with euxinic environments. Abundant bacteriohopanepolyols (BHPs) are mainly produced by anaerobic bacteria. Methylated bacteriohopanepolyols are produced due to low oxygen and high osmolarity. Sedimentary production of BHPs complicates water column reconstructions. Abstract: Bacteriohopanepolyols (BHPs) are a diverse class of bacterial lipids that hold promise as biomarkers of specific microbes, microbial processes, and environmental conditions. BHPs have been characterized in a variety of terrestrial and aquatic environments, but less is known about their distribution and abundance in extreme environmental systems. In the present study, samples taken from the water column and upper sediments of the hyper-euxinic, meromictic Mahoney Lake (Canada) were analyzed for BHPs. Analyses show distinct BHP distributions within the oxic mixolimnion, the chemocline, and the euxinic monimolimnion. Bacteriohopanetetrol (BHT) and unsaturated BHT are the dominant BHPs found in the oxic mixolimnion and at the chemocline, whereas a novel BHP (tentatively identified as diunsaturated aminotriol) dominates the euxinic monimolimnion. Along with the novel BHP structure, composite BHPs (i.e., BHT-cyclitol ether and BHT-glucosamine) were observed in the euxinic monimolimnion and sediments, indicating their production by anaerobic bacteria. Complementary metagenomic analysis of genes involved in BHP biosynthesis (i.e., shc, hpnH, hpnO, hpnP, and hpnR ) further revealed that BHPs in Mahoney Lake are most likely produced by bacteria belonging to Deltaproteobacteria, Chloroflexi, Planctomycetia, and Verrucomicrobia. The combined observations of BHP distribution and metagenomic analyses additionally indicate that 2- and 3-methyl BHTs are produced within the euxinic sediments in response to low oxygen and high osmotic concentrations, as opposed to being diagnostic biomarkers of cyanobacteria and aerobic metabolisms.